The suil suppressor locus in Saccharomyces cerevisiae encodes a translation factor that functions during tRNA(iMet) recognition of the start codon. - Yoon, H J (1992)
We initiated a genetic reversion analysis at the HIS4 locus to identify components of the translation initiation complex that are important for ribosomal recognition of an initiator codon. Three unlinked suppressor loci, suil, sui2, and SUI3, that restore expression of both HIS4 and HIS4-lacZ in the absence of an AUG initiator codon were identified. In previous studies, it was demonstrated that the sui2 and SUI3 genes encode mutated forms of the alpha and beta subunits, respectively, of eukaryotic translation initiation factor 2 (eIF-2). In this report, we describe the molecular and biochemical characterizations of the sui1 suppressor locus. The DNA sequence of the SUI1+ gene shows that it encodes a protein of 108 amino acids with a calculated Mr of 12,300. The sui1 suppressor genes all contain single base pair changes that alter a single amino acid within this 108-amino-acid sequence. sui1 suppressor strains that are temperature sensitive for growth on enriched medium have altered polysome profiles at the restrictive temperature typical of those caused by alteration of a protein that functions during the translation initiation process. Gene disruption experiments showed that the SUI1+ gene encodes an essential protein, and antibodies directed against the SUI1+ coding region identified a protein with the predicted Mr in a ribosomal salt wash fraction. As observed for sui2 and SUI3 suppression events, protein sequence analysis of His4-beta-galactosidase fusion proteins produced by sui1 suppression events indicated that a UUG codon is used as the site of translation initiation in the absence of an AUG start codon in HIS4. Changing the penultimate proline codon 3' to UUG at his4 to a Phe codon (UUC) blocks aminopeptidase cleavage of the amino-terminal amino acid of the His4-beta-galactosidase protein, as noted by the appearance of Met in the first cycle of the Edman degradation reaction. The appearance of Met in the first cycle, as noted, in either a sui1 or a SUI3 suppressor strain showed that the mechanism of suppression is the same for both suppressor genes and allows the initiator tRNA to mismatch base pair with the UUG codon. This suggests that the Sui1 gene product performs a function similar to that of the beta subunit of eIF-2 as encoded by the SUI3 gene. However, the Sui1 gene product does not appear to be a required subunit of eIF-2 on the basis of purification schemes designed to identify the GTP-dependent binding activity of eIF-2 for the initiator tRNA. In addition, suppressor mutations in the sui1 gene, in contrast to suppressor mutations in the sui2 or SUI3 gene, do not alter the GTP-dependent binding activity of the eIF-2. The simplest interpretation of these studies is that the sui1 suppressor gene defines an additional factor that functions in concert with eIF-2 to enable tRNAiMet to establish ribosomal recognition of an AUG initiator codon.